Evaluating Digital Religious Literacy among Madrasah Students in The Era of Algorithm-Driven Social Media - Ari Hasan Ansori; M. Arie Firdaus Heriansyah; Ghina Siti Fitria Heriyanti (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2026)
This study is motivated by the transformation in students’ access to religious information, which is increasingly shaped by algorithm-driven social media platforms. This shift has influenced how madrasah students receive, interpret, and evaluate religious content. In this context, an empirical investigation into students’ digital religious literacy is essential, particularly in responding to the rapid circulation of religious information that is not always verified or validated. The study aims to assess the level of digital religious literacy among Madrasah Aliyah students in the era of social media algorithms. A quantitative approach was employed using an evaluative survey design involving 300 students selected through random sampling techniques. Data were collected using a Likert-scale questionnaire consisting of five indicators: the selection of credible religious sources, information verification, comprehension of religious messages, critical attitudes toward religious content, and digital ethics in information dissemination. Data were analyzed using descriptive statistical methods, including mean scores, percentages, and categorical classification of literacy levels. The findings indicate that students’ digital religious literacy falls within the moderate category, with an average score of 3.28. The lowest performance was observed in the ability to verify information, while social media usage was dominated by TikTok and YouTube as primary sources of religious content. These findings reveal an imbalance between technical literacy and critical literacy, where access and comprehension skills are relatively more developed than evaluative capacities. In conclusion, students’ digital religious literacy is at a moderate level with notable variation across indicators, particularly in information verification, which remains the most critical weakness in their literacy structure.